Health-related quality of life of caregivers of children with low language: Results from two Australian population-based studies. (4th July 2022) - Le, Ha ND; Mensah, Fiona; Eadie, Patricia; Sciberras, Emma; Bavin, Edith L.; Reilly, Sheena; Wake, Melissa; Gold, Lisa
Abstract: Purpose : To examine (1) the association between low language (LL) and caregiver's health-related quality of life (HRQoL), (2) whether persistent LL affects caregiver's HRQoL and (3) whether child social-emotional-behavioural (SEB) difficulties attenuates the association between LL and caregiver's HRQoL. Method : Data were from the Early Language in Victoria Study (ELVS) and the Longitudinal Study of Australian Children (LSAC). Caregiver's HRQoL was measured using the EuroQoL-5 dimensions and the Assessment of Quality of Life-8 dimensions. Language ability was determined using the Clinical Evaluation of Language Fundamentals (CELF)-Preschool-2nd or 4th edition (ELVS) and the Peabody Picture Vocabulary Test-3 rd edition or CELF-4 recalling sentences subscale (LSAC). Child SEB difficulties were measured using the Strengths and Difficulties Questionnaire. Multivariable linear regression was used for the analysis. Result : At 11–12 years, an association between LL and reduced caregiver's HRQoL was found in LSAC, but not in ELVS. Persistent LL from 4–11 years seemed to not affect caregivers' HRQoL in either cohort. Child SEB difficulties attenuated the association between caregiver's HRQoL and LL. Conclusion : Both LL and SEB difficulties contributed to reduced caregiver's HRQoL at children age 11–12 years. Interventions supporting children with LL should consider caregiver's well-being in provision of care that meets families' needs.